Impact of inotuzumab ozogamicin as bridging therapy and tumor burden in CAR-T therapy for B-acute lymphoblastic leukemia - Alcalde-Mellado, Patricia; Ruiz-Maldonado, Victoria; Delgado-Serrano, Javier; Sanoja-Flores, Luzalba; Reinoso-Segura, Marta; Pérez-Ortega, Laura; Sierro-Martínez, Belén; García-Guerrero, Estefanía; Pérez de Soto, Concepción; Pérez-Hurtado, José María; González-Campos, José; Pérez-Simón, José Antonio; et al. (Frontiers in Immunology, 2025)
IntroductionInotuzumab ozogamicin is increasingly being used as bridging therapy (BT) prior to chimeric antigen receptor T-cell (CAR-T) in relapsed/refractory B-cell acute lymphoblastic leukemia (R/R ALL), but its impact on CAR-T expansion and clinical outcomes remains controversial.MethodsThis study analyzed 24 R/R ALL patients receiving tisagenlecleucel after BT (Inotuzumab [n=10] vs. chemotherapy/steroids [n=14]). CAR-T expansion was monitored via multiparametric flow cytometry at different time-points after infusion, with outcomes assessed by event-free survival (EFS), overall survival, and immunophenotypic profiling.ResultsResults indicate that despite lower CAR-T expansion with inotuzumab (median 58.3 vs. 337.7 CAR-T/μL; p=0.011), no difference at 12-month EFS was observed (66.7% vs. 64.3%; p=0.648). However, low tumor burden (LTB) at the time of infusion correlated with improved EFS (81.8% vs. 25% high tumor burden (HTB); p=0.019). Remarkably, inotuzumab achieved superior tumor reduction: 80% of HTB patients achieved LTB vs. 28.6% with chemotherapy (p=0.032). Achieving or maintaining LTB significantly improved EFS in 12 months (81.8% and 100% respectively) vs 25% for patients who maintained HTB. Immunophenotyping revealed a higher proportion of CD8+ stem cell memory (SCM) CAR-T cells at peak of expansion in the inotuzumab group (p=0.036). Interestingly, shorter EFS was observed among those patients who presented a lower percentage of SCM CD8+ CAR-T and lower SCM CD8+CARneg/μL on 28 days and on 90 days after CAR-T therapy.DiscussionOverall, inotuzumab as BT effectively reduces tumor burden but attenuates CAR-T expansion without compromising survival outcomes. As high tumor burden is a dominant driver of relapse and toxicity, the net effect of inotuzumab may be favorable in selected patients.